1996
DOI: 10.1084/jem.184.4.1537
|View full text |Cite
|
Sign up to set email alerts
|

B cells lacking RelB are defective in proliferative responses, but undergo normal B cell maturation to Ig secretion and Ig class switching.

Abstract: SumrlrlaryA number of distinct functional abnormalities have been observed in B ceils derived from pS0/ NF-KB or c-rel knockout mice. RelB, another member of the NF-KB/Rel family of transcription factors, is expressed during the latter stages of B cell maturation and can bind to regulatory sites within the Ig heavy chain locus. Therefore, we tested the ability of B ceils from relB knockout mice (relB -/-) to proliferate, undergo maturation to IgM secretion, and switch to the expression of downstream Ig isotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 30 publications
4
59
1
Order By: Relevance
“…Signaling through CD40 activates both canonical and non-canonical NF-κB pathways, although several lines of evidence suggest that the non-canonical pathway is not required in the response to TD antigens. Thus, B cells lacking p52 are fully capable of appropriate TD antigen responses when transferred [21], and B cells from relB −/− mice, although crippled in their proliferative response, undergo normal IgM secretion and class switching [179]. In contrast to these results, B cells lacking either functional NIK or IKKα, exhibit defective responses [180,181].…”
Section: B-cell Responses Mediated By Nf-κbcontrasting
confidence: 50%
“…Signaling through CD40 activates both canonical and non-canonical NF-κB pathways, although several lines of evidence suggest that the non-canonical pathway is not required in the response to TD antigens. Thus, B cells lacking p52 are fully capable of appropriate TD antigen responses when transferred [21], and B cells from relB −/− mice, although crippled in their proliferative response, undergo normal IgM secretion and class switching [179]. In contrast to these results, B cells lacking either functional NIK or IKKα, exhibit defective responses [180,181].…”
Section: B-cell Responses Mediated By Nf-κbcontrasting
confidence: 50%
“…For example, whereas B cells from p52 À/À mice mount inadequate humoral responses to various T-dependent antigens, they exhibit a normal response following adoptive transfer into rag-1 À/À mice -indicating that this deficit is not intrinsic to B cells (Franzoso et al, 1998). Furthermore, B cells from relB À/À mice, although crippled in their proliferative response, undergo normal IgM secretion and class switching in response to various stimuli (Snapper et al, 1996a). Therefore, non-canonical NF-kB pathway activation downstream of CD40 is probably not required for class switching during T-dependent antigen responses.…”
Section: T-cell Responses Mediated By Nf-kbmentioning
confidence: 99%
“…Preliminary results showed that specific inhibitors of the PI3K, ERK, and p38 pathways (LY294002, PD90859, and SB203580, respectively) did not have a significant effect on the ability of CD40 to increase Pim-1 protein levels (data not shown). Therefore, we focused on the NF-B pathway, which plays a key role in the ability of CD40 to promote the survival of WEHI-231 cells (34,(72)(73)(74) and the proliferation of normal murine B cells (75,76). To determine whether CD40 regulates Pim-1 levels via NF-B, we used two different approaches to inhibit the activation of NF-B.…”
Section: Up-regulation Of Pim-1 By Cd40 Involves the Nf-b Pathwaymentioning
confidence: 99%